GPU accelerated non-illuminated graphical electromagnetic computing method with high accuracy - Li, Jianzhou; Zhang, Zhou; Zheng, Kuisong; Wu, Changying; Gao, Steven (Optik (Stuttgart), 2017)
In this paper, a novel non-illuminated Graphical Electromagnetic Computing Method (NI-GRECO) based on GPU acceleration has been proposed. It has the advantages of high accuracy and efficiency compared to the traditional GRECO method, and does not suffer from the limitation in the illumination model anymore. In this NI-GRECO we also proposed a pixel subdivision technique, which can improve the display accuracy of the target model and then increase computing accuracy. In case of the data output, the method of data extraction by using the Frame Buffer Object (FBO) can also improve computing accuracy. In this way, the data output is no longer subject to color restriction. The extraction accuracy of the normal vector increased from 1/256 to 1/1000000. Additionally, the novel method has a significant speedup, which is up to 36 times than the original GRECO method for a sphere RCS simulation thanks to the parallel GPU processing.